High-power pulsed hybrid semiconductor lasers emitting in the wavelength range 900–920 nm. (October 2021) - Bagaev, T.A.; Gul'tikov, N.V.; Ladugin, M.A.; Marmalyuk, A.A.; Kurnyavko, Yu.V.; Krichevskii, V.V.; Morozyuk, A.A.; Konyaev, V.P.; Simakov, V.A.; Slipchenko, S.O.; Podoskin, A.A.; Pikhtin, N.A.; et al.
Abstract: High-power hybrid semiconductor lasers–thyristors ( λ =900−920nm) consisting of thyristor crystals soldered in series with an integrated semiconductor laser with three emitting sections are studied. A monolithic laser–thyristor with three emitting sections is used as a reference sample. The output power of the triple monolithically integrated laser–thyristor is ∼120 W at a turn-on voltage of 18 V. The turn-on voltage of a hybrid laser–thyristor with three emitting sections is 28 V, and the peak output power reaches ∼170 W.